Giant endocervical polyp: A mimic of mullerian adenosarcoma. A case report with follow-up - Taslima Hossain, MD, FCPS (Histopath); C. James Sung, MD; W. Dwayne Lawrence, MD, MSc (Path); M. Ruhul Quddus, MD, M. Phil (Path) (Elsevier, 2017)
A perimenopausal woman presented with a single recent episode of heavy vaginal bleeding and low hemoglobin level. She has been, however, spotting off and on for the last several years. On examination an ulcerated polypoid lesion was identified protruding through the external os. The lesion raised a clinical suspicion of an adenosarcoma in this perimenopausal patient. The current report describes this rare entity, documents the gross and microscopic features which may mimic adenosarcoma of the mullerian system. Keywords: Giant endocervical polyp, Adenosarcoma